2018
DOI: 10.1017/s0954579418001086
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic–racial identity content and the development of depressive symptoms among Latino adolescents

Abstract: The current study examined the concurrent and prospective associations of ethnic–racial identity content (i.e., centrality, private regard, and public regard) and depressive symptomatology among Latino adolescents. Data were drawn from a longitudinal study of Latino adolescents (N = 148, 53.4% girls) who were 13–14 years old at Wave 1. Results indicated that higher ethnic–racial centrality at Waves 1 and 2 predicted fewer depressive symptoms at Waves 2 and 3, respectively. In addition, more positive private re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 79 publications
(153 reference statements)
3
12
0
Order By: Relevance
“…These findings are consistent with prior studies of typically developing populations, which demonstrate positive associations between individuals' positive feelings about their ethnic-racial group membership and varied adjustment measures (Rivas-Drake et al, 2014). Interestingly, the obtained relations between ERI centrality and youth adjustment were not consistent with prior studies (Cross et al, 2018;Yip et al, 2006), but instead mirrored empirical evidence suggesting that certain ERI processes may lead to negative adjustment outcomes in adversity-exposed populations (Beiser & Hou, 2006).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These findings are consistent with prior studies of typically developing populations, which demonstrate positive associations between individuals' positive feelings about their ethnic-racial group membership and varied adjustment measures (Rivas-Drake et al, 2014). Interestingly, the obtained relations between ERI centrality and youth adjustment were not consistent with prior studies (Cross et al, 2018;Yip et al, 2006), but instead mirrored empirical evidence suggesting that certain ERI processes may lead to negative adjustment outcomes in adversity-exposed populations (Beiser & Hou, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…ERI centrality and ERI private regard were assessed using 14 items adapted from the Multidimensional Inventory of Black Identity (MIBI; Sellers, Rowley, Chavous, Shelton, & Smith, 1997). Although the MIBI was developed to assess ERI in African American samples, the measure has been adapted for use with other ethnic‐racial groups (Cross et al, 2018; Schwartz et al, 2014). ERI centrality was assessed using eight items (e.g., I have a strong attachment to other people from my ethnic‐racial group(s)) and ERI private regard was assessed using six items (e.g., I am proud to be a member of my ethnic‐racial group(s)).…”
Section: 2 Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross, Hoffman, Constante, and Rivas-Drake (2018) investigated the concurrent and prospective associations of ethnic–racial identity content (i.e., centrality, private regard, and public regard) and depressive symptomatology with a longitudinal study of 148 Latino adolescents. Results showed that higher ethnic–racial centrality at Waves 1 and 2 predicted fewer depressive symptoms at Waves 2 and 3, respectively.…”
Section: Equifinality and Multifinality In Cultural Developmentmentioning
confidence: 99%
“…When discussing adolescent identity development, we cannot go without examining ethnic-racial identity development in the context of a racialized society. Ethnic-racial identity is a developmental process where ethnic minority youth explore their ethnicity and race while forming an attachment to their ethnic-racial group [4,5]. The U.S. Census Bureau estimates that by the end of 2020 youth from ethnic-racial minority backgrounds will be half of the population under age 18.…”
Section: Ethnic-racial Identitymentioning
confidence: 99%